Serum oestradiol levels and risk of adverse cardiovascular events associated with gender-affirming oestrogen therapy: a protocol for a systematic review and meta-analysis. Issue 11 (3rd November 2022) - Rytz, Chantal L; Turino Miranda, Keila; Ronksley, Paul E; Dumanski, Sandra M; Saad, Nathalie; Raj, Satish R; Somayaji, Ranjani; Ganshorn, Heather; Newbert, Amelia M; Peace, Lindsay; Ahmed, Sofia B
Abstract : Introduction: The use of gender-affirming oestrogen therapy (GAOT) is an integral part of the gender-affirming transition process for transgender women (assigned male at birth who identify as women) and gender-diverse individuals. However, its use may present significant cardiovascular implications, which may be influenced by systemic oestradiol levels. Therefore, we aim to establish the association between serum oestradiol levels and incidence of adverse cardiovascular events in individuals using GAOT. Methods and analysis: We will conduct a systematic review addressing the association between serum oestradiol levels and risk of adverse cardiovascular events in individuals using GAOT. Our primary outcome is the incidence of adverse cardiovascular events, our secondary outcome is the incidence of cardiovascular-related mortality and our tertiary outcome is cardiovascular-related risk factors. Electronic databases (Cochrane Central Register of Controlled Trials, Embase, MEDLINE and Web of Science) will be searched from inception until September 2022. Two investigators will independently complete screening to determine appropriateness of inclusion. Extracted data will include information on serum sex hormone levels (oestradiol and testosterone), participants, GAOT (route of administration, formulations, dosages and duration of exposure), incidence of cardiovascular outcomes, study quality and risk of bias. Inter-reviewer reliability will be calculated at both phases. Data will be presented both descriptively and meta-analysed using a random effects model, if appropriate. Heterogeneity will be explored and meta-regressed if noted. Ethics and dissemination: Ethics approval is not needed. We will disseminate findings through international conferences, distributions to transgender and gender-diverse support organisations, decision-makers and key stakeholders. The final systematic review will be published in a peer-reviewed journal. Trial registration number: CRD42021247717.